2006
DOI: 10.1002/cphc.200500687
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Non‐Cottrellian Diffusion on the Surface of a Sphere or Truncated Sphere

Abstract: A method is developed whereby spherical and other particles can be derivatised with electroactive species on their surface and then immobilised on the surface of an electrode. The chronoamperometric and voltammetric responses in the limit of reversible electrode kinetics are modelled using a theory of charge movement over the surface of the spheres where this movement is considered as a diffusional process. The model is extended to include different distributions of sphere radii and to model the scenario of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 30 publications
3
28
1
Order By: Relevance
“…For many other cases of functionalized carbon nanotubes (or modified graphite electrodes), Compton et al also identified a square root of scan rate dependency of peak currents [31,32]. These findings have been explained on a theoretical basis by the (non-Cottrellian) propagation of charge on the carbon particle surface [33,34], whereby electrons are assumed to hop from one chemical moiety to another, all being attached to the particle surface, as depicted in Figure 6.7.…”
Section: Theory J183mentioning
confidence: 97%
See 4 more Smart Citations
“…For many other cases of functionalized carbon nanotubes (or modified graphite electrodes), Compton et al also identified a square root of scan rate dependency of peak currents [31,32]. These findings have been explained on a theoretical basis by the (non-Cottrellian) propagation of charge on the carbon particle surface [33,34], whereby electrons are assumed to hop from one chemical moiety to another, all being attached to the particle surface, as depicted in Figure 6.7.…”
Section: Theory J183mentioning
confidence: 97%
“…The charge movement can be treated diffusion-like as electron hopping with coupled solution phase ion motion, contributing to the effective diffusion coefficient [34] (as in the studies cited for the general treatment of a three-phase electrode in Section 6.3.1). Thompson and Compton investigated, from a theoretical standpoint, the case of a spherical microparticle with an electroactive compound on its surface and attached to a solid electrode surface [33,34].…”
Section: Theory J183mentioning
confidence: 99%
See 3 more Smart Citations